"Jim Crow, Yankee Style": Civil Rights and Working-Class Pottstown, Pennsylvania, 1941-1969 - Washington, Matthew (My University, 2019)
Between 1941 and 1969, activists in Pottstown, Pennsylvania, a small working-class borough in Montgomery County, organized and conducted African-American civil rights work. Through the efforts of organizations like the Pottstown NAACP, YMCA, Pottstown Civic League, and the Pottstown Committee on Human Relations, African American and white civil rights activists coordinated such black-centered activism. Also important to these efforts toward combating racial inequality was the advocacy of the town’s major newspaper, the Pottstown Mercury. Although Pottstown, which sits approximately forty miles to the northwest of Philadelphia, was not a large city, this dissertation will demonstrate that it served as an important locale of civil rights activism all the same. Indeed, Pottstown activists’ work and influence even had national impact. By conceptualizing Pottstown as such, this dissertation strays from a dominant interpretive approach utilized by scholarship that examines civil rights work in the twentieth-century urban North. Generally speaking, these studies have stressed large northern cities as the principal centers of civil rights activism. Yet, as this dissertation asserts, if Pottstown never exceeded 27,000 residents from 1941 to 1969, like other small locales in the North, its impact on the nation’s civil rights history was outsized.
Keywords: History; American history